2006
DOI: 10.1101/lm.111506
|View full text |Cite
|
Sign up to set email alerts
|

Latent memory for sensitization in Aplysia

Abstract: In the analysis of memory it is commonly observed that, even after a memory is apparently forgotten, its latent presence can still be revealed in a subsequent learning task. Although well established on a behavioral level, the mechanisms underlying latent memory are not well understood. To begin to explore these mechanisms, we have used Aplysia, a model system that permits the simultaneous study of memory at the behavioral, cellular, and molecular levels. We first demonstrate that robust latent memory is induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
43
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 41 publications
7
43
0
Order By: Relevance
“…The conclusion of our study is consistent with the previously reported findings of Philips et al (2006). Specifically, LTS training of Aplysia has not only overt but also latent learning effects.…”
Section: Learning and Memory 423supporting
confidence: 83%
See 3 more Smart Citations
“…The conclusion of our study is consistent with the previously reported findings of Philips et al (2006). Specifically, LTS training of Aplysia has not only overt but also latent learning effects.…”
Section: Learning and Memory 423supporting
confidence: 83%
“…Had the modulatory component of the network been potentiated by 4-d training, sensitization would have become apparent earlier than 25 min after BST (i.e., at the 15-min time point). This study thus, along with the recent report by Philips et al (2006), constitutes an initial step in the cellular and molecular characterization of biological processes that can facilitate learning and memory. Long-term sensitization training primes the animal for further learning.…”
Section: Learning and Memory 423mentioning
confidence: 99%
See 2 more Smart Citations
“…CIHR Author Manuscript CIHR Author Manuscript [22,23]. In cultures, these messages might already be present at the synapse because of the synaptic growth induced by culturing the neurons.…”
Section: Cihr Author Manuscriptmentioning
confidence: 99%